On vibrations in Green-Naghdi thermoelasticity of dipolar bodies - Marin M.; Chirilă A.; Codarcea L.; Vlase S. (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2019)
This study is concerned with the theory of thermoelasticity of type III proposed by Green and Naghdi, which is extended to cover the bodies with dipolar structure. In this context we construct a boundary value problem for a prismatic bar which is subjected to some harmonic in time vibrations. For the oscillations whose amplitudes have the frequency lower than a critical value, we deduce some estimates for describing the spatial behavior.